A beacon or just a landmark? Reflections on the 2004 Royal Society/Royal Academy of Engineering report: Nanoscience and nanotechnologies: opportunities and uncertainties (Responsible Nano Forum, 2009)
"On 29th July 2004, the Royal Society and Royal Academy of Engineering released their seminal report Nanoscience and Nanotechnologies: opportunities and uncertainties. 5 years on, to mark this milestone The Responsible Nano Forum invited opinion formers from science, risk, investment, ngos, unions, business and consumer groups to reflect on the legacy of the report and what still remains to be done. The report "A beacon or just a landmark', features 28 contributions from a range of individuals and organisations in the UK and internationally. The Foreward is written by Dr Andrew Maynard, Chief Science Advisor to the Woodrow Wilson Project on Emerging Nanotechnologies and features contributions from two members of the original RS/RAEng working group. Whilst the Forum has resisted the temptation to summarise or synthesise the contributions, in its Introduction Hilary Sutcliffe seeks to draw observations from the report, and from the development of nanotechnologies over last five years, to consider development of future emerging technologies."